Evolution of the nutritional support pattern in Pediatric Intensive Care - Leite, Heitor Pons; Iglesias, Simone Brasil de Oliveira; Faria, Cacilda Maria de Santana; Ikeda, Angela Maria; Albuquerque, Maria Paula de; Carvalho, Werther Brunow de (São Paulo Medical Journal, 1998)
OBJECTIVES: to evaluate patterns of usage and monitoring of nutritional support in a Pediatric ICU of a teaching hospital and the role of an education program in nutritional support given throughout the resident physician training. DESIGN: in a historical cohort study, records from children who received nutritional support during the year 1992 were analyzed. Thereafter a continuing education program in Nutritional Support was conveyed to the residents. In a second phase of the study, the same parameters were reevaluated in children who received nutritional support throughout the year 1995. SETTING: Pediatric Intensive Care Unit of Department of Pediatrics, Escola Paulista de Medicina. PATIENTES: all the children who were given nutritional support during a period of five days or more. Based on this criteria 37 children were selected for the first phase of this study, and 35 for the second one. INTERVENTION: the education program included theoretical lectures about basic themes of nutritional support and journal article reading sessions. It was given to successive groups of residents on a weekly schedule. MEASUREMENTS: Daily records of fluid, protein, caloric and micronutrient supply, nutritional assessment and metabolic monitoring. RESULTS: In the first phase of the study, an exclusively parenteral route was utilized for 80.5%, and a digestive route 19.5% of the time period. Nutritional assessment was performed on 3 children; no patient had the nutritional goals set. The nitrogen to nonprotein calories ratio and the vitamin supply were inadequate, whilst the supply of trace elements was adequate except for zinc. Nutritional monitoring was performed on almost all patients but without uniformity. In the second phase, the exclusive parenteral route was used for 69.7% and the digestive route for 30.3% of the time period; no significant increase in the use of the digestive route was detected. The nonprotein calories to nitrogen ratio and micronutrient supply were adequate. The frequency of nutritional assessment increased, but deficiency in nutritional monitoring and infrequent enteral feeding were still detected. CONCLUSION: There were deficiencies in the implementation of nutritional support, which were partially corrected in the second phase of the study by the training of the residents. Reinforcement of the education program, which should be applied to the whole medical staff, and the organization of a multidisciplinary team in charge of coordinating the provision of nutritional support are suggested.